(3GdGfJUGQ dSeGY Hf GdMLGQs - (3eMeO Hf YHO Gddg Hf eMeO GdbjSj GdOeTbqj GdTGaYqj, TeS GdOjf, GdTgjQ HGHf fGUQ GdOjf,J (B842 (3g` s ((3fhQ GdOjf Ydi GdOejGWi GdeUQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdGfJUGQ ef Phi GdEMf dMeGd GdBKGQ GdfHhjg hGdSff aEf Gddg YR hLd GcQe gPg GdGeg s
(3BNQgG (B:s
(3BNQ GdGfJUGQ dSeGY GdMLGQ , Ydbg eDdag eMeO Hf CHj HcQ YHO Gddg GHf eMeO Hf CMeO YaG Gddg Yfge HcQeg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B35 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs